2011
DOI: 10.1111/j.1741-6612.2011.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Cities, environmental stressors, ageing and chronic disease

Abstract: This study provides empirical evidence that older long-term Australian urban residents are more likely to have a non-infectious chronic disease, which may be associated with environmental exposure, than those living in rural locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…In particular, when examining the prevalence rate of individual diseases, it could be seen that diseases with distinct lifestyle influences, such as hypertension and diabetes, were significantly more prevalent in urban regions. Contrary to the pervasive argument for a rural disadvantage to health, several previous studies have reported lower rates of chronic disease in rural regions . Although Liu et al .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, when examining the prevalence rate of individual diseases, it could be seen that diseases with distinct lifestyle influences, such as hypertension and diabetes, were significantly more prevalent in urban regions. Contrary to the pervasive argument for a rural disadvantage to health, several previous studies have reported lower rates of chronic disease in rural regions . Although Liu et al .…”
Section: Discussionmentioning
confidence: 82%
“…[23][24][25] Although Liu et al suggest the reported better health in rural areas might be due to an underreporting or underdiagnosis as a result of a lack of proper medical infrastructure, other studies cite the healthier lifestyles of rural areas, including less exposure to environmental pollutants, non-Westernized diets and non-sedentary habits, as protective factors of multimorbidity. [23][24][25] Also, the prevalence of traditional Chinese medicine health centers and basic primary healthcare clinics in village regions might facilitate access to primary care among rural residents, allowing for more efficient management of chronic conditions in villages as compared with in the cities. 26 The difference in multimorbidity rates between urban and rural Korea draws a similar yet different picture.…”
Section: Discussionmentioning
confidence: 99%
“…In the Household Income and Labour Dynamics in Australia (HILDA) survey, age, housing location and area sociodemographic status were associated with a long-term illness. 10 Whilst others have reported poorer health in rural areas, in this dataset people in outer urban areas with SEIFA Quintile 2 (second most disadvantaged) were 12 times more likely to have a long-term condition than those in rural areas from SEIFA Quintile 5 (least disadvantaged). This finding may be due to the homogeneity of the cohort: most lived in urban, freestanding dwellings.…”
Section: Housing Affordabilit Ymentioning
confidence: 66%
“…For example, Brennan and colleagues confirmed a relationship between renting and poorer health utility (measured with the EuroQol5D) and well‐being. In the Household Income and Labour Dynamics in Australia (HILDA) survey, age, housing location and area sociodemographic status were associated with a long‐term illness . Whilst others have reported poorer health in rural areas, in this dataset people in outer urban areas with SEIFA Quintile 2 (second most disadvantaged) were 12 times more likely to have a long‐term condition than those in rural areas from SEIFA Quintile 5 (least disadvantaged).…”
Section: Housing Affordabilitymentioning
confidence: 76%
“…Current research evidence suggests that well-being in late life is closely related to the physical environment, which is an important factor mediating aging experiences and opportunities (Black, O'Loughlin, Kendig, & Wilson, 2012;Buffel, Phillipson & Scharf, 2012;Wahl & Oswald, 2010). Urban studies also confirm that the nature of the neighborhood has a significant impact on mobility, independence, and quality of life of older people living in the community (Phillipson, 2010;Plouffe & Kalache, 2010;Windsor, Pearson, Crisp, Butterworth, & Anstey, 2012).…”
Section: Older People and The Urban Environmentmentioning
confidence: 88%